Desenvolvimento de larvas de Steindachneridion sp. em diferentes condições de refúgio eluminosidade - Feiden, Aldi (2006)
The influence of luminosity and of the use of refuges on the initial development of Steindachneridion sp. Garavello (Siluriforme: Pimelodidae) larvae was evaluated. A thousand larvae 18.02 mm high and 62.2 mg weight were used in an entirely randomized design, with five treatments and four replicates, in 35 L-aquarium during 22 days. The treatments consisted on the following environments: darkness without refuges, clear with artificial refuge, darkness with artificial refuge, clear with natural refuge and clear without refuge. All larvae received the same feeding during the experiment. The best survival rates were found for darkness without refuges, clear with artificial refuge and clear without refuge, with 84, 76 and 70%, respectively. The best development was in darkness and without refuges. The treatment darkness with artificial refuge provided significant differences in relation to the other treatments as far as survival and weight are concerned, showing high heterogeneity for weight. Environment without refuges are the most appropriate for the larval development of this specie.